Who was Pierre Marie? - MARANHÃO-FILHO, Péricles; VINCENT, Maurice (Arquivos de Neuro-Psiquiatria, 2020)
In this manuscript we pay a tribute to Pierre Marie (1853-1940), highlighting his great contribution to medicine and neurology describing several diseases and syndromes. We mainly emphasize aspects of his personal life and personality traits. Considered one of the three greatest neurologists of the late nineteenth and early twentieth centuries, his brilliant career began at La Salpêtrière, followed by the development of a neurological school at Hospice Bicêtre. Pierre Marie had numerous disciples around the world, including Brazil, and published on various neurological and endocrinological themes. Back to La Salpêtrière, he concluded his professional life as a Neurology leader. However, after retirement, his demise was sad and lonely
Keywords: Neurology; History; Pierre Marie